Reality orientation therapy for a patient with schizophrenia and paranoid delusions: A case study report - Bian Wintana, Dwi Amalia Putri; Apriliyani, Ita (JOURNAL OF Mental Health Concerns, 2026)
Background: Schizophrenia is a chronic mental disorder that significantly affects cognitive function and behavior, frequently characterized by prominent delusions in Paranoid Schizophrenia. Delusional nursing problems are marked by severe distortions of reality perception, which impair patients’ ability to think logically and interact appropriately with their environment. Purpose: To describe and evaluate the implementation of Reality Orientation Therapy (ROT) in addressing delusional nursing problems in a patient with Paranoid Schizophrenia. Method: This research employed an intensive descriptive case study conducted over four days to illustrate and assess the application of Reality Orientation Therapy in Mrs. Y at Liliy 4 Ward, Seorojo Hospital. The primary intervention focused on the consistent, non-confrontational application of ROT through orientation to person, place, and time, integrated with collaborative pharmacological management. Results: The findings demonstrated that Reality Orientation Therapy was substantially effective in correcting cognitive distortions and enhancing reality-based thinking abilities. This improvement was evidenced by significant clinical progress and increased scores in reality-oriented thought content, indicating that the delusional nursing problem experienced by Mrs. Y was successfully resolved. Conclusion: Reality Orientation Therapy can be considered an effective nursing intervention for reducing delusions and improving reality-based thinking in patients with Paranoid Schizophrenia when implemented consistently and collaboratively with pharmacological treatment.   Keywords: Delusions; Paranoid Schizophrenia; Reality Orientation Therapy (ROT).